Application of Public Relations Management Concept as A Communication Strategy for Corporate Social Responsibility Campaign #BeautyDiQuity PT Luxury Cantika Indonesia (Luxcrime) - Wibowo, Wini Elia; Permassanty, Tanty Dewi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Bisnis dan Informatika Kwik Kian Gie, 2023)
Luxcrime conducted a public relations program campaign, in 2023 by choosing the campaign moment to coincide with International Women's Day with the theme